Cu and Zn removal by adsorption using ash from palm oil factory - Al-Madhoun, W.A.; Isa, M.H.; Ramli, N.A.; Adlan, M.N.; Hameed, B.H.; Farooqi, I.H. (2005)
The presence of heavy metals, such as Cu and Zn, in wastewater can be hazardous to the environment. From the view point of environmental protection, it is important that their concentrations be limited to permissible levels. Technologies for heavy metals removal include ion exchange, chemical precipitation, reverse osmosis, etc. which are often ineffective or expensive. Adsorption is commonly used for the removal of heavy metals from aqueous solutions. The process would be economical if the adsorbent is easily and cheaply available in abundance and that it requires minimal or no pre-treatment; for expensive pre-treatment procedures would add to the overall treatment cost. The present study focuses on Cu and Zn removal by adsorption using ash from a palm oil factory. The effect of agitation time, pH and adsorbent mass on the removal of Cu and Zn was studied and isotherms were generated to describe the removal of the metals. The results show that the ash was an effective adsorbent for the removal of Cu and Zn.